Changes in spatial patterns of biomass energy potential from biowaste in China from 2000 to 2020 - Lang, Lixia; Chen, Yanbi; Liu, Yan; Wu, Jianxi; Yu, Yongkun; Wang, Yan; Chen, Xingpeng; Zhang, Zilong (Frontiers in Energy Research, 2023)
Developing biomass energy to alleviate the worldwide energy crisis has become a global priority. In order to ensure the optimal utilization of biomass energy, it is necessary to calculate a country’s biomass energy potential, so as to provide support for the formulation of biomass energy macro policies, especially for the sustainable supply of raw materials. This study constructs the biomass inventory, including crop straw, livestock manure, forest residues and municipal solid waste, and estimates the potential of the biomass energy supply of 31 provinces (autonomous regions and municipalities) in China from 2000 to 2020. The changes in the spatial pattern of the biomass energy supply are explored. Taking 2020 as a targeted year, the spatial patterns of biomass energy density defined as the biomass energy per land area and per rural person is then analyzed. The aims of this study are to assess the capacity of biomass resources in China to support a bio-based economy and provide a reference for China’s biomass energy policy formulation and strategic layout. The results show that from 2000 to 2020, China’s biomass energy converted into coal equivalent generally showed a fluctuating upward trend from 139141.73 104 tce in 2000 to 146133.20 104 tce in 2020, with an average annual growth rate of 0.24%. The biomass energy is dominated by livestock manure and crop straw and the four types of biomass energy show different changes but with an overall upward trend. The spatial patterns of the biomass energy potential are generally uneven, with significant inter-provincial differences and obvious regional differences in cold and hot spots. In 2020, the energy density of the biomass energy potential is characterized by "two highs and two lows", i.e., the biomass energy density per unit land area is "high in the east and low in the west" and the per capita biomass energy density in rural areas is "high in the north and low in the south".